Child life specialist: the chief executive officer perspective - Fehlen, Phylicia (University of Wisconsin--Stout. Research Services, 2016)
Within the pediatric hospital environment, child life specialists are changing the practice of pediatric medicine, turning traumatic encounters into growth promoting experiences with lasting effects on the health and well-being of hospitalized children (Tobin, 2013). Child life specialists are invaluable members of the health care team trained specifically in addressing the psychosocial needs of young patients, through an assortment of techniques aimed at creating a sense of normalcy in the young patient’s life during hospitalization. Sadly, the general population doesn’t understand the importance of a child life specialist until they witness first-hand the invaluable support they provide to a child. The lack of knowledge of the child life field has caused child life specialists to be seen as supplementary to other professionals within a pediatric hospital. This qualitative case study investigated the perceptions of the child life field from the perspective of a decision maker, a Chief Executive Officer (CEO) of a pediatric hospital in urban Minnesota. The purpose of this study was to gain more knowledge from a primary decision- maker about the value a CEO places on child life in an age of austerity. This study found crucial implications for practitioners; it’s vital that child life specialists are aware of how others within the hospital view them, particularly those that are making decisions about budgets. They will be able to address these perceptions and assist health care professionals in better understanding the value and goals of the child life department.
Research article with tables.
Keywords: child life specialist; child life department; Child Life Council; Pediatrics